1998
DOI: 10.1046/j.1365-2885.1998.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of enrofloxacin after intravenous, intramuscular and oral administration in houbara bustard (Chlamydotis undulata macqueenii)

Abstract: The in-vitro activity of enrofloxacin against 117 strains of bacteria isolated from bustards was determined. Minimum inhibitory concentrations for 72% of the Proteus spp., E. coli, Salmonella spp. and Klebsiella spp. (n = 61) and for 48% of the Streptococci spp. and Staphylococci spp. (n = 31) were < or = 0.5 microg/mL. The minimum inhibitory concentration (MIC) of 76% of Pseudomonas spp. (n = 25) was < or = 2 microg/mL. Fourteen strains were resistant to concentrations > or = 128 microg/mL. The elimination ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
7
9
3
Order By: Relevance
“…The t 1/2b of enrofloxacin recorded in this study was similar to values reported for greater rheas [17] and emus [18], but much slower than the results obtained in ostrich [19], whereas, Anadon et al [12] in chickens, Dimitrova et al [13] in turkey and Bailey et al [20] in houbara bustard observed longer elimination t 1/2b . The t 1/2b obtained in the present study indicates that emu tends to eliminate enrofloxacin slower than ostrich and faster than chickens and turkeys.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The t 1/2b of enrofloxacin recorded in this study was similar to values reported for greater rheas [17] and emus [18], but much slower than the results obtained in ostrich [19], whereas, Anadon et al [12] in chickens, Dimitrova et al [13] in turkey and Bailey et al [20] in houbara bustard observed longer elimination t 1/2b . The t 1/2b obtained in the present study indicates that emu tends to eliminate enrofloxacin slower than ostrich and faster than chickens and turkeys.…”
Section: Resultssupporting
confidence: 89%
“…As compared to the total body clearance (Cl B ) [17]. The Cl B values for chickens (4.8 mL/ min kg); [12] and houbara bustard (5.7 mL/min kg); [20] are comparatively lesser than the result obtained in the present study. Cox et al [26] explained that the clearance and volume of distribution were proportional to body weight.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…administration was similar to that found in chickens (Anado¨n et al, 1995;Bugyei et al, 1999;GarciaOvando et al, 1999;Knoll et al, 1999) and muscovy ducks (Intore et al, 1997). Its distribution and elimination are much slower than found in other bird species^hawks and owls (Herrenstein et al, 2000), psitacine birds (Flammer and Whitt-Smith, 2002) and houbara bustard (Bailey et al, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…This value suggests that marbofloxacin is widely distributed extravascularly as occurs with other fluoroquinolones. However, it is lower than the distribution volume of enrofloxacin (Bailey et al ., 1998; García Ovando et al ., 1999; Knoll et al ., 1999).…”
Section: Pharmacokinetic Parameters After Intravenous (Iv) Adminismentioning
confidence: 99%